Direct-current output of silicon–organic monolayer–platinum Schottky TENGs: Elusive friction-output relationship - Lyu, Xin; MacGregor, M.; Liu, J.; Darwish, Nadim; Ciampi, Simone (2023)
Triboelectric nanogenerators (TENGs) are an emerging energy harvesting technology able to convert ubiquitous mechanical energy into electricity. Friction, static charging and flexoelectricity are all involved in the mechanism underpinning TENG operation, but their relative contribution has remained elusive. Here we used dynamic and static conductive atomic force microscopy (C-AFM) measurements on monolayer-modified silicon crystals to detect evidence of a relationship between friction and zero-bias current, and between pressure and the direction of the putative flexovoltage. We demonstrate that a static electricity-related tribovoltage is probably responsible for a friction excess, and that surprisingly this friction excess is found to be dependent on the doping level and type of the silicon substrate. Such friction excess is however no longer measurable once current is allowed to flow across the junction. This observation points to an electrostatic origin of friction in silicon-based Schottky TENGs, and suggests that the zero external bias DC current is at least in part an electronic flow to neutralize static charges. Further, the sign of the zero-bias current, but not its magnitude, is independent of the semiconductor doping type, which is again suggestive of surface statics being a main contributor to the zero-bias output rather than exclusively a space-charge effect. We also reveal the presence of a junction flexovoltage under pressures common in AFM experiments (GPa), even for negligible lateral friction. In a static Pt–monolayer–n-type Si junction the flexovoltage carries the same sign as the tribovoltage, and can reach such magnitude to overwrite external voltages as high as 2 V. The immediate implication is that the flexovoltage is likely to have i) a strong contribution to the zero-bias output of a n-Si Schottky TENG, ii) a negative effect on the output of a p-Si TENG, and iii) its detection can be straightforward, as we discovered that flexoelectricity manifests as an “inverted diode”: a n-type Si–platinum diode with negligible current even when the n-type material is negatively biased as long as the “static” diode remains under a large normal pressure.